Song of the mysteries - Wurts, Janny (Wurts, Janny. Wars of Light and Shadow., 2025)
The hugely anticipated final volume of The Wars of Light and Shadow brings this widely acclaimed, masterful epic fantasy series to its powerful, earth-shattering close.